2014
DOI: 10.1287/mnsc.2013.1824
|View full text |Cite
|
Sign up to set email alerts
|

Gender Interactions Within the Family Firm

Abstract: We analyze whether gender interactions at the top of the corporate hierarchy affect corporate performance. Using a comprehensive data set of family-controlled firms in Italy, we find that female directors significantly improve the operating profitability of female-led companies. To mitigate endogeneity concerns, we assess executive transitions using a triple-difference approach complemented by propensity score matching and instrumental variables. Finally, we show that the positive effect of female interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
167
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 228 publications
(178 citation statements)
references
References 50 publications
9
167
0
2
Order By: Relevance
“…Consistent with Amore et al (2014), which found that the proportion of female directors on the board could improve the performance of a female CEO, we found that the presence of other female leaders on a firm's board and/or top management team can weaken the in Tables 3 and 4 with data on board chair successions and found that board chair succession with gender change has no effect on post-succession performance or the successor board chair's early routine or non-routine departure. Our findings highlight the importance of the presence of other female leaders in the firm's upper echelon as well as the inside origin of the successor.…”
Section: Gender Change Effect In Ceo Successionsupporting
confidence: 55%
See 2 more Smart Citations
“…Consistent with Amore et al (2014), which found that the proportion of female directors on the board could improve the performance of a female CEO, we found that the presence of other female leaders on a firm's board and/or top management team can weaken the in Tables 3 and 4 with data on board chair successions and found that board chair succession with gender change has no effect on post-succession performance or the successor board chair's early routine or non-routine departure. Our findings highlight the importance of the presence of other female leaders in the firm's upper echelon as well as the inside origin of the successor.…”
Section: Gender Change Effect In Ceo Successionsupporting
confidence: 55%
“…In a context of family-controlled firms in Italy, Amore et al (2014) provided some empirical evidence to the benefits of "female interactions" at the top. 3 The authors found that the profitability of firms led by female CEOs was significantly improved with an increasing number of female directors on the board.…”
Section: The Presence Of Other Female Leaders In a Firm's Upper Echelonmentioning
confidence: 99%
See 1 more Smart Citation
“…Smith et al (2006), using both OLS and IV methods (where the fraction of women in top management is instrumented by the education of male CEO's wives), find that the proportion of women in top management jobs tend to be positively associated with firm performance in a panel of large Danish firms, but the association becomes largely insignificant once one controls for firm fixed effects. Amore et al (2013) find that only the joint presence of women in CEO and governance positions significantly improves firm performance in a sample of family-controlled firms in Italy. 5 Using a subset of the data that we use in this paper, Laible (2013) finds a slight negative correlation between the proportion of women in top management and establishment performance.…”
Section: Literature Reviewmentioning
confidence: 73%
“…Alternatively, female executives, being more attuned to the needs of female employees, may be more likely to promote female friendly policies, such as provision of child care or specific mentoring programs. 4 The goal of this paper is to explicitly investigate how the gender composition of the top layer of management affects firm and employee outcomes. To this purpose, we use a large linked employer-employee data set on German establishments between 1993 and 2012.…”
mentioning
confidence: 99%